Analysis of the Field of Meaning in Endorsement Product Captions - Syafroni, Roni Nugraha (Institute of Educational, Research, and Community Service, 2024)
Instagram, a highly popular social media platform in Indonesia, has undergone a transformation, evolving beyond being merely a source of entertainment to serving as a medium for providing education to the public. The term